Natural history of skeletal muscle mass changes in chronic kidney disease stage 4 and 5 patients: an observational study - John, Stephen G.; Sigrist, Mhairi K.; Taal, Maarten W.; McIntyre, Christopher W. (Public Library of Science, 2013)
Cross-sectional studies in dialysis demonstrate muscle wasting associated with loss of function, increased morbidity and mortality. The relative drivers are poorly understood. There is a paucity of data regarding interval change in muscle in pre-dialysis and dialysis-dependant patients. This study aimed to examine muscle and fat mass change and elucidate associations with muscle wasting in advanced CKD.